Motivation of Students at SMA Negeri 8 Yogyakarta in Participating in Table Tennis Extracurricular Activities - Setiawan, Sendy; Ermawan, Ermawan; Fanani, Zainuddin (Global Education Journal, 2025)
Modern education has transcended its traditional role as a mere transfer of knowledge and has evolved into a crucial foundation for shaping students’ character, social values, and holistic potential. This study aims to describe the level of student motivation at SMA Negeri 8 Yogyakarta in participating in table tennis extracurricular activities and to identify the dominant form of motivation between intrinsic and extrinsic factors. The research employed a descriptive quantitative approach involving 45 students who actively participated in the program. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability. The results revealed that most students demonstrated moderate to high levels of motivation, with intrinsic factors such as personal enjoyment and the desire for self-improvement being more influential than extrinsic factors like teacher encouragement or environmental support. These findings underscore the importance of a developmental approach tailored to students’ interests and personal needs in managing extracurricular programs. The study contributes valuable insights for formulating strategies to enhance student participation in less popular sports activities at school.